Surface behaviour of as-cast Al-Fe intermetallic composites - Mohan S.; Srivastava S. (My University, 2025)
In order to produce energy-efficient material for tribological applications, Al-Fe inter-metallic composites have been produced by liquid metallurgy route. Iron content of the composites varies from 1.67 to 11.2 wt.%. These composites have been tested for their wear properties at different parameters. Debris and wear tracks have been studied in detail to see the surface effects during dry sliding and have been correlated to wear properties. Observations show that low loads and sliding velocities are dominated by oxidative debris and largely covered wear track surface with smooth oxide layer is observed. Whereas metallic debris dominates at higher loads and sliding velocities and highly deformed wear track surface with deep grooves and gross delamination were observed. Further, wear rate is seen to increase continuously with load whereas with sliding velocity it attains a minima after initial decrease and then increases continuously. Low solubility of iron supports the formation of FeAl3 and an increase in hardness from 95 to 179 VHN continuously improves the wear resistance with increase in percentage iron. © Springer Science+Business Media, Inc. 2006.